2022
DOI: 10.1038/s41467-022-29896-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screens identify GATA6 as a proviral host factor for SARS-CoV-2 via modulation of ACE2

Abstract: The global spread of SARS-CoV-2 led to major economic and health challenges worldwide. Revealing host genes essential for infection by multiple variants of SARS-CoV-2 can provide insights into the virus pathogenesis, and facilitate the development of novel therapeutics. Here, employing a genome-scale CRISPR screen, we provide a comprehensive data-set of cellular factors that are exploited by wild type SARS-CoV-2 as well as two additional recently emerged variants of concerns (VOCs), Alpha and Beta. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…This tool has been tested using multiple datasets to offer robust and wide applicability [1620]. Of note, this tool can be used to detect hits that were previously unnoticed, by aggregating common hits from different experiments, as is the case of GATA6 proviral gene for SARS-CoV-2, which we identified as the 4 th hit using rearranged Biering et al datasets [19], and has been confirmed by Israeli et al [21].…”
Section: Introductionmentioning
confidence: 57%
“…This tool has been tested using multiple datasets to offer robust and wide applicability [1620]. Of note, this tool can be used to detect hits that were previously unnoticed, by aggregating common hits from different experiments, as is the case of GATA6 proviral gene for SARS-CoV-2, which we identified as the 4 th hit using rearranged Biering et al datasets [19], and has been confirmed by Israeli et al [21].…”
Section: Introductionmentioning
confidence: 57%
“…Located on chromosome Xp22 , ACE2 is an X-linked, dosage-sensitive gene known to be transcriptionally regulated by EP300, SP-1, CEBP, GATA3, and HNF1/4 115,116 . Recent efforts have aimed to identify novel ACE2 modifiers, uncovering PIAS1, SMAD4, BAMBI , KDM6A , and GATA6 111,117 . DPP4 , which is situated on chromosome 2q24, e ncodes a serine exopeptidase that regulates glucose homeostasis 118,119 .…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the CRISPR screens was robust, as indicated by the top resistance hits of viral entry receptors identified, such as dipeptidyl peptidase-4 (DPP4) for MERS-CoV, human aminopeptidase N (ANPEP) for HCoV-229E, and ACE2 for SARS-CoV, SARS-CoV-2, and HCoV-NL63 [ [69] , [70] , [71] , [72] , [73] , [74] ]. Unlike other coronaviruses, HCoV-OC43 lacks a recognized proteinaceous receptor, but alternatively relies on sialic acid [ 75 ] or glycosaminoglycans (Neu5, 9Ac2) for cell entry [ 76 ].…”
Section: Identification Of Host Factors In Sars-cov-2 Replication By ...mentioning
confidence: 99%